PENGEMBANGAN MEDIA BUKU INTERAKTIF BERBASIS BUKU CERITA “PIPPI LANGSTRUMPF” SEBAGAI ZUSATZMATERIAL UNTUK KETERAMPILAN MEMBACA BAHASA JERMAN NIVEAU A2 - Az Zahro', Dzakiyyah; Wahyuningsih, Fahmi (LATERNE, 2025)
This research aimed to develop an interactive book-based learning medium adapted from the children’s story Pippi Langstrumpf as supplementary material (Zusatzmaterial) to enhance reading skills in German at the A2 level. The study adopted a research and development (R&D) approach, employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) during the analysis, design, and development stages. Data were collected through classroom observations at SMAN 15 Surabaya and validations by a subject-matter expert, a media expert, and a practitioner. The findings revealed that the interactive book medium achieved feasibility scores of 98% (subject-matter expert), 94% (media expert), and 92% (practitioner), categorizing it as highly feasible. This interactive book combined narrative texts with engaging elements such as pop-ups, pull tabs, hidden objects, peek-a-boo features, and participation components, which were considered effective in fostering reading interest and skills. The study was expected to contribute both theoretically and practically to the field of language learning.